Examining the Gender Differentials in the Application for STEM Fields: Findings from the University of Lagos - Attoh, Franca; Obashoro-John, Yemisi; Quadri, Maryam; Olowu, Femi; Durojaiye, Abimbola (Unilag Journal of Humanities, 2019)
Building on secondary data, this paper seeks to make two contributions to literature. First, to present a description of the sex differentials in course applications into Nigerian universities, using the University of Lagos as a sample and second, to describe the variation in the selection of courses in the fields of Science, Technology, Engineering and Mathematics (STEM) by prospective students that are females. Findings showed that female applications for degree programmes were higher than male applications in most fields, including some core science fields which involve human-oriented professions like pharmacology and medicine. Nevertheless, the overall statistics revealed that the proportion of male applicants were fractionally higher during the four sessions under review. The sex differentials were highest in engineering and environmental sciences fields where male applications outnumbered female applications by a ratio of about three to one. Furthermore, female applicants were more likely to choose biological, peopleoriented and care-centred fields, leading to female apathy towards engineering and other technical programmes, especially those with mathematics, physics and geography as core subjects. We, therefore, recommend the development of nationwide programmes aimed at dispelling gendered misconceptions about certain fields, especially STEM fields. This is very essential in a world where science and technology define national economies. Nigeria cannot afford to leave half her population behind.